PENGARUH PENGGUNAAN LIMBAH KULIT KOPI TERFERMENTASI (Aspergillus niger) DENGAN ARAS BERBEDA DALAM RANSUM TERHADAP PERTUMBUHAN AYAM BURAS - W. Y. K., N. M. INTAN; MASTIKA, I M.; NURIYASA, I M. (Majalah Ilmiah Peternakan; Vol 21 No 1 (2018): Vol 21, No 1 (2018), 2018)
An experiment was carried out to study the effect of fermented and not fermented coffee skin waste to the growth of kampong chicken. A completely randomized design, with five treatments and five replications were used so there are 25 experiment units and each unit consisted of 4 cockerels. The Treatments as of P0: diet without coffee skin waste (diet control), P1: diet containing non fermented coffee skin waste 10%, P2: diet containing non fermented coffee skin waste 20%, P3: diet containing fermented coffee skin waste 10% and P4: diet containing fermented coffee skin waste 20%. The variables measured were performance including the final body weight, weight gain, feed consumption, feed conversion ratio, water consumption, and carcass characteristics. Based on result,it can be concluded that kampong chicken given diet with additional fermented and non fermented coffee skin waste up to 20% level has no effect on the growth of kampong chicken age 3-11 weeks, but there is a tendency that the best diet is10% fermented coffee skin.